2017
DOI: 10.1590/1677-5449.000517
|View full text |Cite
|
Sign up to set email alerts
|

A incidência regional do tromboembolismo venoso no Brasil

Abstract: Background: Several studies conducted in areas with temperate climates have suggested that the incidence of venous thromboembolism (VTE) varies depending on seasonal climatic fluctuations. However, no studies have been conducted comparing areas with semi-arid climate with areas with temperate climates. Objectives: To analyze whether there is a correlation between the incidence of VTE in areas with semi-arid climates and areas with temperate climates in Brazil. Methods: Retrospective data were acquired for pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 12 publications
0
4
0
5
Order By: Relevance
“…2 Na literatura, diversos estudos relacionam a presença de TEV com a variação climática. No Brasil, Ohki et al 4 relataram maior incidência de TEV nos estados do Sul, onde as temperaturas são mais baixas. A incidência de casos de TEV nesses locais apresentou uma média de 2,86 para cada 100.000 habitantes.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…2 Na literatura, diversos estudos relacionam a presença de TEV com a variação climática. No Brasil, Ohki et al 4 relataram maior incidência de TEV nos estados do Sul, onde as temperaturas são mais baixas. A incidência de casos de TEV nesses locais apresentou uma média de 2,86 para cada 100.000 habitantes.…”
Section: Introductionunclassified
“…A incidência de casos de TEV nesses locais apresentou uma média de 2,86 para cada 100.000 habitantes. 4 Tal síndrome clínica aumenta exponencialmente com a idade, mesmo com a aplicação de estratégias de prevenção. 5 A mulheres são mais comumente afetadas na juventude, sobretudo no puerpério.…”
Section: Introductionunclassified
“…It can be stated that there is a negative linear correlation between V1 and V3, just as Ohki and Bellen identified a moderate negative correlation (ρ = -0.65; p < 0.01) between average regional temperature and the incidence of venous thrombosis. 6 It can also be observed that the values for the correlation between V1 and V3 are closer to the imaginary straight line than the values for the correlation between V1 and V2. This invites the conclusion that the relationship between the values of the variables V1 and V3 is stronger than the relationship between V1 and V2, even though the directions are opposite.…”
mentioning
confidence: 75%
“…Although elevated sweating during heat contributes to hemoconcentration, this may be offset by increased water intake. Besides, in the Brazilian study, an association of an increase in thromboembolism incidents with a decrease in air temperature was revealed [ 66 ]. Moreover, the meta-analysis [ 4 ] showed that hematocrit in humans is higher in winter than in summer, and in regions where atmospheric pressure is significantly lower in summer compared to winter, summer decrease in hematocrit is maximal.…”
Section: Discussionmentioning
confidence: 99%